PENGARUH GAYA KOMUNIKASI PIMPINAN DAN GANGGUAN DOMESTIK PADA PELAKSANAAN BEKERJA DARI RUMAH - Dwi Anggraeni, Eliza; Kurniawati, Dewi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
The purpose of writing this journal is to discuss the influence of leadership styles and domestic disturbances on the implementation of working from home. The methodology used is qualitative research with a literature study by collecting and analyzing everything from books, articles, and journals that discuss related to the communication style of organizational leaders and domestic disturbances that have an impact on the implementation of working from home. Leadership style affects the implementation of work from home policies. Autocratic leadership style can be an obstacle in the implementation of working from home, while charismatic, transactional and transformational leadership styles will be a separate support for the implementation of working from home. There is a significant relationship between domestic interference with work from home life and home life in organizational policies, It takes a very high employee commitment in the organization when implementing a work from home policy for the realization of a balance between personal life and work (work life balance).